Traditional Chinese Medicine for HIV-Associated Acute Herpes Zoster: A Systematic Review and Meta-Analysis of Randomized Trials. (18th February 2022) - Jiang, Yue; Zheng, Ruo-Xiang; Yu, Ze-Yu; Zhang, Xiao-Wen; Li, Jing; Lan, Hui-Di; Qiao, Shu-Yu; Han, Mei; Cao, Hui-Juan; Robinson, Nicola; Liu, Jian-Ping
Abstract : Background . Herpes zoster (HZ) is a common infection in individuals with acquired immunodeficiency syndrome (AIDS) patients. Traditional Chinese medicine (TCM) has been used widely in clinical practice for HZ, which remains not supportive of evidence. This review aimed to evaluate the effectiveness and safety of TCM in treating HIV-associated HZ. Methods . Nine electronic databases were searched for randomized controlled trials (RCTs) testing TCM in treating HIV-associated HZ. Data were extracted on citations, interventions, and outcomes, by two authors independently. For the quality evaluation, Cochrane risk-of-bias tool 2.0 was used. Meta-analyses were performed by Revman5.3 software. Effect estimation presented as risk ratio (RR) for dichotomous data and mean difference (MD) for continuous data with their 95% confidence interval (CI). Results . Twelve RCTs ( n  = 644) were included; the majority of them had a high or unclear risk of bias. Meta-analysis showed that pain intensity (VAS 0–5) in the Chinese herbal medicine (CHM) group was lower than it in the drugs group (MD = −0.87, 95% CI [−1.69, −0.04], two trials, n  = 93). Duration of herpes-related pain (days) of patients in the combination group was shorter than those in the drugs group (MD = −9.19, 95% CI [−16.73, −1.65], n  = 144). The incidence of postherpetic neuralgia (PHN) in the combination group was lower than in the drugs group (RR = 0.49, 95% CI [0.25, 0.99], n  = 202). As for cure rate (complete absence of pain and herpes), two trials showed that CHM was better than drugs (RR = 1.58, 95% CI [1.13, 2.22], n  = 93), five trials showed combination treatment was better than drugs (RR = 1.40, 95% CI [1.08, 1.82], n  = 224). The cure rate in the acupuncture group was more than that in the drugs group (RR = 1.99, 95% CI [1.18, 3.36], n  = 120). Four trials reported adverse effects and found no serious adverse events occurred. Conclusion . CHM and acupuncture demonstrate more benefits than drugs in pain relief, cure rate improvement, and incidence reduction of PHN. However, given the data limitation and TCM therapies' diversity, the conclusions need to be verified in future trials.